The development and validation of the Norfolk QOL-DN, a new measure of patients' perception of the effects of diabetes and diabetic neuropathy - Vinik, Etta J; Hayes, Risa P; Oglesby, Alan; Bastyr, Edward; Barlow, Patricia; Ford-Molvik, Stephanie L; Vinik, Aaron I (Diabetes technology & therapeutics, 2005)
This study was designed to develop and validate a patient-reported outcomes measure, sensitive to the different features of diabetic neuropathy (DN)-small fiber, large fiber, and autonomic nerve function. The review of 1,000 structured patient interviews guided the development of 28 items pertaining specifically to the symptoms and impact of large fiber, small fiber, and autonomic nerve function. These items, in addition to 14 generic health status items and five general information items formed the 47-item Norfolk Quality of Life Questionnaire-Diabetic Neuropathy (QOL-DN). Items were grouped according to small fiber, large fiber, and autonomic nerve function, symptoms, and activities of daily living (ADL). Scores in individual domains were aggregated to provide a total score. Item groupings were tested for their ability to distinguish between the effects of specific nerve fiber deficits in 262 subjects-81 healthy controls (C), 86 controls with diabetes (DC), and 95 patients with DN-using one-way analysis of variance (ANOVA). Internal consistency was estimated using Cronbach's alpha coefficient. Test-retest reliability over a 4-6-week period was estimated by intra-class correlation coefficients and ANOVA on data of a subset of patients and controls. Differences between DN subjects and both DC and C subjects were significant (P < 0.05) for all item groupings. Total quality of life (QOL) scores correlated with total neuropathy scores. The ADL, total QOL, and autonomic scores were greater in DC than C subjects (P < 0.05). Intra-class correlation coefficients were > 0.9 for most domains. Internal consistency of the fiberspecific domains using Cronbach's alpha was > 0.6 and up to 0.8. The fiber-specific domains of the QOL-DN demonstrated acceptable reliability and ability to discriminate between subjects with and without neuropathy. Not surprisingly, the DN group scored significantly (P < 0.05) higher than either of the two control groups (i.e., greater impairment). The positive scores for the DC group in the ADL and autonomic domains suggest that diabetes per se impacts these aspects of QOL.